Analisis Faktor-Fator yang Mempengaruhi Penggunaan Aplikasi Investasi Reksadana Online pada Generasi Millenial dan Generasi Z - Jasmine Aubrey Andrea; Jarot S Suroso (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2022)
This study aims to analyze the driving factors that can influence individuals in using mutual funds Bibit application. The proposed model has factors from the The theory of technology adoption (TAM) is implemented in this study to analyze how technology adoption of online mutual fund investment with millennial as the main object of research. This research is a quantitative research with a survey method by distributing online questionnaires. Sampling using purposive sampling method. This study Used 5 internal variables and 3 external variables which are Perceived Security, Perceived Trust and User Interface After gathering 168 data respondents, it is found that there are several factors that have positive significance to Actual System Use to adopt online mutual fund application, namely Perceived Security, User Interface, Perceived Usefulness, Perceived Ease of use, Attitude Toward Use and Behavioral Intention to Use. Meanwhile, Perceived Trust have no significance to Actual System Usage of Bibit application. This finding will be useful for online mutual fund application developers to transform conventional mutual fund to online platforms format.